The Implementation of Early Detection of Security and Order Disruptions in Class I Penitentiary of Bandar Lampung in View of Law Number 22 of 2022 - Baharudin, Baharudin; Raja, Mario Nazir Lumban (The Future of Education Journal, 2026)
The Class I Correctional Facility of Bandar Lampung faces serious challenges in maintaining security and order due to overcrowding conditions and the limited number of correctional officers. These circumstances have the potential to trigger security and order disturbances if not anticipated through systematic preventive measures. Law Number 22 of 2022 on Corrections, particularly Article 81, emphasizes early detection as a strategic instrument in preventing security and order disturbances within correctional institutions. This study aims to examine the implementation of early detection of security and order disturbances at the Class I Correctional Facility of Bandar Lampung based on the provisions of Article 81 of Law Number 22 of 2022 on Corrections. In addition, this research analyzes the factors influencing the effectiveness of early detection in correctional practice. The research employs an empirical juridical method with a qualitative approach. Data were collected through a literature review of relevant laws and regulations as well as legal literature, and through interviews with correctional officials and officers directly involved in security management and inmate development. The collected data were analyzed using descriptive qualitative analysis to assess the consistency between normative legal provisions and their implementation in practice. The findings indicate that the implementation of early detection of security and order disturbances at the Class I Correctional Facility of Bandar Lampung has generally been conducted in accordance with the normative framework of Law Number 22 of 2022. This is reflected in practices such as monitoring inmate behavior, supervising residential block environments, and strengthening coordination among correctional officers. However, the effectiveness of its implementation remains suboptimal due to limitations in human resources, overcrowding conditions, and inadequate supporting facilities and infrastructure. This study concludes that early detection is a strategic instrument in maintaining security and order within correctional institutions. Therefore, strengthening human resources, improving facilities and infrastructure, and optimizing supervision systems are necessary to ensure that early detection can be implemented more effectively and sustainably.